Income Generation Through Varietal Selection of Rabi Onion in KymorePlateau of Madhya Pradesh (Indian Journal of Extension Education, 2011)
A field study was conducted to study the income generate through varietal selection of rabi onion in Kymore Plateau of Madhya Pradesh during 2010-11 at Krishi Vigyan Kendra, Rewa (M.P.). The treatments comprising of nine varieties of onion collected from various sources were tested. There were nine treatment assigned to randomized block design with three replications. The results showed non significant variation in number of plant per square meter and significant variation in number of leaves per plant, plant height, neck thickness, length of bulb, width of bulb, length: width of bulb, weight of 100 bulbs and bulb yield among the various varieties. The maximum number of plant per square meter (65 plant), plant height (34.10 cm), width of bulb (7.60 cm), weight of 100 bulbs (10.147 kg) and bulb yield (249.33 q/ha) were recorded in Agrifound Light Red and maximum number of leaves per plant (14.0) in Pusa Red, neck thickness (1.1 cm) in Bhima Sweta, length of bulb (5.63 cm) in Pusa Red and length: width of bulb (0.83) were observed in Pusa Madhavi. Minimum number of plant per square meter (63.0 plant), number of leaves per plant (8.0), width of bulb (6.53 cm), weight of 100 bulbs (6.960 kg) and bulb yield (210.67 q/ha) were noted in Bhima Shakti and minimum plant height (32.27 cm) in N-2-4-1, neck thickness (0.70 cm) in Pusa Madhavi and Agrifound Dark Red, length of bulb (4.60 cm) in Pusa Madhavi and length: width of bulb (0.65) were found in Agrifound Light Red. Agrifound Light Red was superior in yield compared to other varieties and high income generate through Agrifound Light Red (Rs 1, 99,464/ha).